Masculinity Representation in Lithuanian Interwar Press Advertising - Bankauskaitė-Sereikienė, Gabija; Stravinskaitė, Raminta (Respectus Philologicus, 2016)
The analysis of this article focuses on normative interwar masculinity images. As advertising is an integral part of modern society revealing its face, the analysis is based on press advertisements collected from interwar magazines. Hegemonic features such as: a super man, a successful careerist, the man of a family, a hedonistic and narcissistic man were analysed. The analysis is focused on verbal and non-verbal expressions. The results have shown that the image of a super man was mostly related to the body and its size, ability to do a hard work. Main details – classic suit and luxury attribute such as a car usually represented a good social status and described a man as a successful careerist. It was noted that during the interwar period hegemonic masculinity was expressed by self-confidence. It was represented by a hedonistic, level-headed man images. The construct of the patriarch of the family started to be criticized during the interwar period and was slowly replaced by a new image of a careful man and husband.